Effect of grain orientation on the CFRP-to-LVL bond. (15th November 2017) - Subhani, Mahbube; Globa, Anastasia; Al-Ameri, Riyadh; Moloney, Jules
Abstract: In recent years, carbon fibre reinforced polymer (CFRP) was found to be an effective technique to strengthen or retrofit timber beams. One of the timber sub-products, laminated veneer lumber (LVL), has two different surfaces (laminate and grain face) in the direction of its grain on which CFRP is usually applied in order to increase its flexural strength. To enhance the shear strength of an LVL, CFRP is applied in the direction perpendicular to the LVL grain. In this study, the application of CFRP on different surfaces and grain directions of an LVL is analysed experimentally and theoretically. For the theoretical interpretation, the values related to the parameters that incorporate the effect of surface and grain direction are proposed and verified. Moreover, maximum bond strength, fracture energy and bond stiffness are determined to assess the bond strength between these two materials.